A efetividade do “Programa de Recebimento e Monitoramento de Efluentes não Domésticos” à promoção da segurança hídrica ecossistêmica do Rio Uberabinha em Uberlândia - Bazilio, Ana Paula (2023)
Water scarcity culminated in the theme of water security, which can be understood as the balance between supply and demand for water, both in contingency situations and in extreme weather events. The continuous growth of the population followed by a deficient planning of the territorial occupation also contributes to the hydric stress and, mainly, to the increase of the effluents. Uberlândia implemented the PREMEND – Program for Receiving and Monitoring Non-Domestic Effluents, aiming to reduce the polluting load of non-domestic effluents, considering that conventional treatment does not process several components of industrial effluents, impacting on aquatic life and on the quality of the river’s water Uberabinha. The study consisted of four stages: i. temporal analysis of adhesions to PREMEND since 2013, flow of treated effluents and amounts collected with sanctions; ii. collection of raw and treated effluents and water upstream and downstream of the effluent release; iii. assessment of effluent treatment efficiency and water quality according to the IQA – Water Quality Index and the Water Safety Classification; and saw. association between the water quality of the Uberabinha River, the annual adhesion rate, the flow of treated effluents and the BOD and COD efficiency levels. The results showed that from Decree No. 13,481 of June 22, 2012, which instituted PREMEND until the first half of the evaluated period, there was a greater number of adhesions and an increase in the number of collections. Regarding the efficiency of effluent treatment, the parameters have been kept within the limits, but the best results occurred in the middle of the analyzed period. According to the IQA and the water security classification, there is a change in water quality between the upstream and downstream points. Finally, there were no changes in results between the rainy and dry seasons and the increase in the number of adhesions over the years did not impact water quality